PADDY SEED BAGGING MACHINE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
A simple manually operated seed bagging machine made of locally available materials using local manufacturing technology was designed, fabricated, and tested for collecting and bagging of grains(paddy) dried on concrete pavement. The invention belongs to the technical field of agricultural machines, and relates to a tool applied when grains are collected after being aired, in particular to a manual seed bagging machine. Grains are automatically loaded into a hooper by pushing the manual grain bagging machine with hand. then the grains in the hopper falls on the conveyor belt, which is arranged to the machine, by the rotation of the conveyor belt the grains move up wards and fall in the bag which is arranged to the machine. A simple manually operated grain collector and bagging had the following major components: frame, wheel, long pipe, vertical stand frame (bars), horizontal bars, collector, bar, motor, conveyor belt and a metal hopper. Radial flat bladed type base plate, slot bar, sweeping box, bagging area, frame and the lifting system by conveyor belt and motor. Results showed significant differences on the collecting capacity, and noise level. Other parameters such as collecting efficiency, air velocity, augmented cracked grain percentage. The design was made based on certain assumptions and calculations and the collector was built, tested and evaluated.